Low–molecular-weight Heparin and Recurrent Placenta-mediated Pregnancy Complications: A Meta-Analysis of Individual Patient Data From Randomized Controlled Trials. Issue 3 (September 2017) - Rodger, M.A.; Gris, J.C.; De Vries, J.I.P.; Martinelli, I.; Rey, É.; Schleussner, E.; Middeldorp, S.; Kaaja, R.; Langlois, N.J.; Ramsay, T.; Mallick, R.; Bates, S.M.; et al.
Abstract : ( Lancet . 2016;388:2629–2641) Placenta-mediated pregnancy complications include preeclampsia, birth of a small for gestational age (SGA) neonate, placental abruption, and late pregnancy loss. They are significant contributors to maternal and neonatal morbidity and mortality. Patients experiencing these complications are also at risk of placenta-mediated complications occurring in subsequent pregnancies. Effective preventive measures for these complications are generally lacking. The current investigators had previously published a study-level meta-analysis that indicated low–molecular-weight heparin (LMWH) could reduce the risk of recurrence. However, there was significant heterogeneity in that study so they decided to perform an individual patient data meta-analysis to evaluate the efficacy of LMWH to prevent recurrent placenta-mediated complications in subsequent pregnancies.